REFLEKSI EKSISTENSI JENDER DALAM NOVEL JURANG KEADILAN KARYA PIPIET SENJA - Hengki Fikra; Abdurahman Abdurahman; Muhammad Ismail Nasution (Jurnal Bahasa dan Sastra, 2013)
The purpose of this research is to describe novel structural gender exitences that are  reflected on women characters involving. Gender eksistences as domestic sector and gender existences as public sector on novel Jurang Keadilan composed by Pipiet Senja this research discusied aboud the nature of novel, novel structural, fiction analisys approach, the nature of feminism, and the nature of gender existence. This is a qualitative research by using descriptif method to analyze novel structurals in general and mimesys approach to analyze the gender existence an a novel. First edition of the object of this research is Jurang Keadilan written by Pipiet Senja printing 1 dzuhijjah 1431 H/Desember 2010. Collection data were conducted by there steps. (1) reading and understanding the novel, (2) marking the parts that indicate the gender existence, (3) identifying characters to find the similaritles with the research problem, (4) classifying sentences and paragraph that could visualize pictures of women in Jurang Keadilan novel. After the data collected, those data will be analyzed by these following steps: (1) describing the novel structural, (2) classifying the gender existence data, (3) interpreting the gender exixtence on women characters, (4) resulting data that has been analyzed and interpreted and (5) reporting the research result.